Self-regulated learning-based digital module development to improve students' critical thinking skills - Kusmaharti, Dian; Yustitia, Via (Al-Jabar: Jurnal Pendidikan Matematika, 2022)
Learning technology needs to support improving critical thinking skills in the 21st century. Self-regulated learning-based digital module can be used to support students’ independent learning. The aims of this study are (1) to describe a valid digital module based on self-regulated learning; (2) to evaluate and describe the practicality of the digital module based on self-regulated learning; (3) to determine the effectiveness of the digital module based on self-regulated learning on students' critical thinking skills. The method used is Research and Development with the ADDIE development model. The results of the study are (1) the developed digital module based on self-regulated learning is declared valid; (2) the digital module based on self-regulated learning is stated to be practical as indicated by the response and implementation in the good category; (3) students' critical thinking skills in the experimental class are better than the control class. Generally, the self-regulated learning-based digital modules are valid, practical, and effective.